QORAQALPOG‘ISTON TABIIY RESURSLARI VA ULARDAN FOYDALANISH ISTIQBOLLARI - Beкimbetova, G.N. (SCIENCE and SOCIETY, 2024)
The article talks about minerals, mineral resources and their reserves in the territory of the Republic of Karakalpakstan, as well as the large-scale work being carried out on their use in the national economy.
Keywords: minerals; raw materials; mines; mineral salts; oil; mine gases; phosphorite deposits; geographical location; properties; rock salt; ecology